Designing Opportunities for Mathematical Creativity: Three Ways to Modify an Existing Course. Issue 3 (15th March 2020) - Mayes-Tang, Sarah
Abstract: Creativity plays an important role in mathematics, but it can be overlooked in undergraduate courses. This article describes three ways an existing first-year math seminar was modified to increase its focus on creativity: introducing readings and discussions related to creativity, drawing connections to creativity in other disciplines, and adding an open-ended project. Suggestions are included for instructors who wish to incorporate one or all of the modifications in their own courses.